Pediatric Cancer Therapeutics Development - DiMartino, Jorge; Reaman, Gregory H.; Smith, Franklin O.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive overview of the scientific, medical, regulatory, and economic considerations associated with the discovery, development, and delivery of novel therapeutics for children with cancer. Co-authored by a diverse team from academic, government, and industry backgrounds, the book describes the steps in the process from the identification of a promising therapeutic target to the evaluation of drug candidates in the various phases of clinical testing and regulatory review. Throughout, special emphasis is placed on the unique biology of pediatric malignancies and the medical and social needs of children and their families. In providing a firm grounding in the drug development process, the book will be of value to all with an interest in how medicines currently used to treat pediatric cancer were made available. This includes trainees as well as established practitioners and others participating in translational and clinical research in the academic setting.
History of Drug Development -- Target Identification/Validation and Drug Discovery -- Non-Clinical Toxicology -- Study Design and Biostatistics -- Personalized Medicine and Its Impact on Study Design -- Gene and Cellular Therapy -- The Pharma/Biotech Model for Drug Development -- Clinical Research Organizations -- Role of Patients and Advocates in Cancer Therapeutics -- Development -- International Regulatory Agencies -- Ethical Considerations in Cancer Therapeutics Development -- Future Directions: Jorge DiMartino. .
Keywords: Oncology; Pediatrics; Oncology; Pediatrics; Neoplasms; Child; Infant; Neoplasms -- therapy